Phylogenomic analysis of UDP glycosyltransferase 1 multigene family in Linum usitatissimum identified genes with varied expression patterns - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Gupta, Vidya S. (BMC Genomics, 2012)
Background: The glycosylation process, catalyzed by ubiquitous glycosyltransferase (GT) family enzymes, is a prevalent modification of plant secondary metabolites that regulates various functions such as hormone homeostasis, detoxification of xenobiotics and biosynthesis and storage of secondary metabolites. Flax (Linum usitatissimum L.) is a commercially grown oilseed crop, important because of its essential fatty acids and health promoting lignans. Identification and characterization of UDP glycosyltransferase (UGT) genes from flax could provide valuable basic information about this important gene family and help to explain the seed specific glycosylated metabolite accumulation and other processes in plants. Plant genome sequencing projects are useful to discover complexity within this gene family and also pave way for the development of functional genomics approaches. Results: Taking advantage of the newly assembled draft genome sequence of flax, we identified 137 UDP glycosyltransferase (UGT) genes from flax using a conserved signature motif. Phylogenetic analysis of these protein sequences clustered them into 14 major groups (A-N). Expression patterns of these genes were investigated using publicly available expressed sequence tag (EST), microarray data and reverse transcription quantitative real time PCR (RT-qPCR). Seventy-three per cent of these genes (100 out of 137) showed expression evidence in 15 tissues examined and indicated varied expression profiles. The RT-qPCR results of 10 selected genes were also coherent with the digital expression analysis. Interestingly, five duplicated UGT genes were identified, which showed differential expression in various tissues. Of the seven intron loss/gain positions detected, two intron positions were conserved among most of the UGTs, although a clear relationship about the evolution of these genes could not be established. Comparison of the flax UGTs with orthologs from four other sequenced dicot genomes indicated that seven UGTs were flax diverged. Conclusions: Flax has a large number of UGT genes including few flax diverged ones. Phylogenetic analysis and expression profiles of these genes identified tissue and condition specific repertoire of UGT genes from this crop. This study would facilitate precise selection of candidate genes and their further characterization of substrate specificities and in planta functions.

Proteome profiling of flax (linum usitatissimum) seed: characterization of functional metabolic pathways operating during seed development - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Journal of Proteome Research, 2012)
Flax (Linum usitatissimum L.) seeds are an important source of food and feed due to the presence of various health promoting compounds, making it a nutritionally and economically important plant. An in-depth analysis of the proteome of developing flax seed is expected to provide significant information with respect to the regulation and accumulation of such storage compounds. Therefore, a proteomic analysis of seven seed developmental stages (4, 8, 12, 16, 22, 30, and 48 days after anthesis) in a flax variety, NL-97 was carried out using a combination of ID-SDS-PAGE and LC-MSE methods. A total 1716 proteins were identified and their functional annotation revealed that a majority of them were involved in primary metabolism, protein destination, storage and energy. Three carbon assimilatory pathways appeared to operate in flax seeds. Reverse transcription quantitative PCR of selected 19 genes was carried out to understand their roles during seed development. Besides storage proteins, methionine synthase, RuBisCO and S-adenosylmethionine synthetase were highly expressed transcripts, highlighting their importance in flax seed development. Further, the identified proteins were mapped onto developmental seed specific expressed sequence tag (EST) libraries of flax to obtain transcriptional evidence and 81% of them had detectable expression at the mRNA level. This study provides new insights into the complex seed developmental processes operating in flax.
Keywords: alpha-linolenic acid; carbon flux; Digital expression analysis; flax seed development; MSE; secoisolariciresinol diglucoside

Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis

Genome-wide identification and characterization of nucleotide binding site leucine-rich repeat genes in linseed reveal distinct patterns of gene structure - Kale, Sandip M.; Pardeshi, Varsha C.; Barvkar, Vitthal T.; Gupta, Vidya S.; Kadoo, Narendra Y. (Genome, 2013)
Plants employ different disease-resistance genes to detect pathogens and to induce defense responses. The largest class of these genes encodes proteins with nucleotide binding site (NBS) and leucine-rich repeat (LRR) domains. To identify the putative NBS-LRR encoding genes from linseed, we analyzed the recently published linseed genome sequence and identified 147 NBS-LRR genes. The NBS domain was used for phylogeny construction and these genes were classified into two well-known families, non-TIR (CNL) and TIR related (TNL), and formed eight clades in the neighbor-joining bootstrap tree. Eight different gene structures were observed among these genes. An unusual domain arrangement was observed in the TNL family members, predominantly in the TNL-5 clade members belonging to class D. About 12% of the genes observed were linseed specific. The study indicated that the linseed genes probably have an ancient origin with few progenitor genes. Quantitative expression analysis of five genes showed inducible expression. The in silico expression evidence was obtained for a few of these genes, and the expression was not correlated with the presence of any particular regulatory element or with unusual domain arrangement in those genes. This study will help in understanding the evolution of these genes, the development of disease resistant varieties, and the mechanism of disease resistance in linseed.
Keywords: Flax; in silico gene expression; motif analysis; NBS-LRR; Phylogenetic analysis; Promoter analysis

Integrative omics analysis in Pandanus odorifer (Forssk.) Kuntze reveals the role of Asparagine synthetase in salinity tolerance - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain; Mundhe, Swapnil; Kadoo, Narendra Y. (Scientific Reports, 2019)
Pandanus odorifer (Forssk) Kuntze grows naturally along the coastal regions and withstands salt-sprays as well as strong winds. A combination of omics approaches and enzyme activity studies was employed to comprehend the mechanistic basis of high salinity tolerance in P. odorifer. The young seedlings of P. odorifer were exposed to 1 M salt stress for up to three weeks and analyzed using RNAsequencing (RNAseq) and LC-MS. Integrative omics analysis revealed high expression of the Asparagine synthetase (AS) (EC 6.3.5.4) (8.95 fold) and remarkable levels of Asparagine (Asn) (28.5 fold). This indicated that salt stress promoted Asn accumulation in P. odorifer. To understand this further, the Asn biosynthesis pathway was traced out in P. odorifer. It was noticed that seven genes involved in Asn bisynthetic pathway namely glutamine synthetase (GS) (EC 6.3.1.2) glutamate synthase (GOGAT) (EC 1.4.1.14), aspartate kinase (EC 2.7.2.4), pyruvate kinase (EC 2.7.1.40), aspartate aminotransferase (AspAT) (EC 2.6.1.1), phosphoenolpyruvate carboxylase (PEPC) (EC 4.1.1.31) and AS were up-regulated under salt stress. AS transcripts were most abundant thereby showed its highest activity and thus were generating maximal Asn under salt stress. Also, an up-regulated Na+/H+ antiporter (NHX1) facilitated compartmentalization of Na+ into vacuoles, suggesting P. odorifer as salt accumulator species.

Approach to nigericin derivatives and their therapeutic potential - Sahu, Amit Kumar; Said, Madhukar S.; Hingamire, Tejashri; Gaur, Megha; Khan, Abujunaid; Shanmugam, Dhanasekaran; Barvkar, Vitthal T.; Dharne, Mahesh S.; Bharde, Atul A.; Dastager, Syed G. (RSC Advances, 2020)
A new nigericin analogue that has been chemically modified was synthesized through a fluorination process from the parent nigericin, produced from a novel Streptomyces strain DASNCL-29. Fermentation strategies were designed for the optimised production of nigericin molecule and subjected for purification and structural analysis. The fermentation process resulted in the highest yield of nigericin (33% (w/w)). Initially, nigericin produced from the strain DASNCL-29 demonstrated polymorphism in its crystal structure, i.e., monoclinic and orthorhombic crystal lattices when crystallised with methanol and hexane, respectively. Furthermore, nigericin produced has been subjected to chemical modification by fluorination to enhance its efficacy. Two fluorinated analogues revealed that they possess a very potent antibacterial activity against Gram positive and Gram negative bacteria. To date, the nigericin molecule has not been reported for any reaction against Gram-negative bacteria, which are increasingly becoming resistant to antibiotics. For the first time, fluorinated analogues of nigericin have shown promising activity. In vitro cytotoxicity analysis of fluorinated analogues demonstrated tenfold lesser toxicity than the parent nigericin. This is the first type of study where the fluorinated analogues of nigericin showed very encouraging activity against Gram-negative organisms; moreover, they can be used as a candidate for treating many serious infections.

Glucosinolate induces transcriptomic and metabolic reprogramming in Helicoverpa armigera - Jagdale, Shounak; Tellis, Meenakshi; Barvkar, Vitthal T.; Joshi, Rakesh S. (3 Biotech, 2021)
Glucosinolates protect plants from herbivory. Lepidopteran insects have developed resistance to glucosinolates which is well studied. However, the molecular effects of glucosinolate intake on insects are unexplored. To elucidate this, we performed transcriptomics and metabolomics of sinigrin-fed Helicoverpa armigera. Transcriptomics exhibits significant dysregulation of 2375 transcripts, of which 1575 are upregulated and 800 downregulated. Gene Ontology analysis of differentially expressed genes reveals that key hydrolases, oxidoreductases, and transferases are majorly affected. The negative impact of sinigrin is significant and localized in the endomembrane system and mitochondria. It also disturbs various biological processes such as regulation of protein metabolism and cytoskeletal organization. Furthermore, H. armigera putative myrosinase-like enzymes may catalyze the breakdown of sinigrin to allyl isothiocyanate (AITC). AITC targets the electron transport chain causing oxidative stress. KEGG pathway enrichment shows significant upregulation of oxidative phosphorylation, glutathione metabolism and amino acid metabolism. Activation of these pathways induces glutathione synthesis for sinigrin detoxification. Differential gene expression indicates upregulation of glutathione S-transferase and succinate dehydrogenase suggesting mitochondrial impact. Transcriptomics data correlated with metabolomics show changes in serine, methionine, ornithine, and other metabolite levels. It corroborates well with the transcript alterations supporting the increased glutathione production. Thus, our data suggest that sinigrin generates oxidative stress in H. armigera and insects alter their metabolic wiring to overcome sinigrin-mediated deleterious effects.
Keywords: Detoxification; Glucosinolate; Glutathione; mitochondria; Oxidative stress

Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Exploring the core microbiota in scented rice (Oryza sativa L.) rhizosphere through metagenomics approach - Dhondge, V. Harshal; Barvkar, Vitthal T.; Paul, Dhiraj; Dastager, Syed G.; Pable, Anupama A.; Nadaf, Altafhusain B. (Microbiological Research, 2022)
Rice is a major food crop cultivated around the globe. Specially scented rice varieties are of commercial importance but they are low-yielding. The rhizospheric microflora plays a significant role in improving yield and aroma. However, the core microbiome of the scented rice rhizosphere is comparatively less explored. Here, we analyzed the core microbiome associated with the rhizosphere of the scented (Ambemohar-157 and Dehradun basmati) in comparison with non-scented rice (Kolam and Arize 6444 Gold) cultivated at two different geoclimatic zones of India (Maharashtra and Uttarakhand) using the metagenomics approach. The alpha and beta diversity analysis showed that the microbial communities associated with scented and non-scented varieties significantly changes with respect to richness, diversity, and evenness. The taxonomic profiling revealed the variation in composition, diversity, and abundance of the microbiome in terms of phyla and genera associated with scented rice varieties over non-scented. The cluster analysis distinguishes the microbial communities based on their geographical positions. The core microbiome analysis revealed that scented rice rhizosphere shelters distinct and unique microbiota. 28.6 % of genera were exclusively present only in the scented rice rhizosphere. The putative functional gene annotation revealed the high abundance of genes related to the biosynthesis of 2-acetyl-1-pyrroline (2AP) precursors in scented rice. The precursor feeding analysis revealed proline as a preferred substrate by 2AP synthesizing bacteria. The 2AP precursor proline and proline metabolism genes showed a positive correlation. The scented rice-specific rhizobacteria pointed out in this study can be used as bioinoculants for enhancing aroma, yield, and sustainable rice cultivation.
Keywords: Metagenome; Microbial community; Microbiome; Oryza sativa; Rhizosphere; rice

Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites

Bacterial communities and diversity of western ghats soil: a study of a biodiversity hotspot - Ghare, Uma; Narvekar, Simran; Lodha, Tushar; Mallebhari, Rubiya; Dastager, Syed; Barvkar, Vitthal T.; Dhotre, Dhiraj; Karmalkar, Nitin R.; Pable, Anupama A. (Current Microbiology, 2023)
The Western Ghats is one of India's mega-diversity hotspots and an ecologically and geologically important area for the diversity of endemic plants and animals. The present study provides insights into the aerobic bacterial diversity and composition of the soils of North Western Ghats located in Maharashtra state (NWGM), India. The samples for the culture-dependent study were collected from 6 different locations namely Malshej Ghat, Bhimashankar, Lonavala, Mulshi, Tail-Baila, and Mahabaleshwar. A total of 173 isolates were obtained from the different samples, which belonged to Proteobacteria (43%), Firmicutes (36%), and Actinobacteria (19%). Sequences of 15 strains shared <= 98.7% similarity (a species cut-off) which represent potential novel species. Metagenomic analysis revealed the presence of Actinobacteria and Proteobacteria as the most dominant phyla at both MB and MG. However, both sites showed variation in the composition of rare phyla and other dominant phyla. This difference in bacterial community composition could be due to differences in altitude or other physicochemical properties. The functional prediction from the amplicon sequencing showed the abundance of carbohydrate, protein, and lipid metabolism which was corroborated by screening the isolated bacterial strains for the same. The present study has a unique take on microbial diversity and defines the importance of community assembly processes such as drift, dispersal, and selection. Such processes are relatively important in controlling community diversity, distribution, as well as succession. This study has shown that the microbial community of NWGM is a rich source of polysaccharide degrading bacteria having biotechnological potential.

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Rashmi, Deo; Ansari, Waquar A.; Kadoo, Narendra Y.; Barvkar, Vitthal T.; Deshmukh, Rupesh; Nadaf, Altafhusain B. (Acta Physiologiae Plantarum, 2023)
Soil salinity is a major environmental constraint causing huge losses in crop production. Pandanus odorifer (Forssk.) Kuntze is an aromatic monocot plant species belonging to the family Pandanaceae, which grows naturally on the saline soils along the coasts of Asia, Southeast Asia, and Polynesia. The plants are dioecious and highly fertile, and the consistent saline sprays, strong winds, and severe soil salinity hardly affect their growth and fertility. Hence, understanding the mechanism of high salinity tolerance in P. odorifer could provide major advances in overcoming salinity stress in crop plants. In the present study, we analyzed control (0 M NaCl) and treated (1 M NaCl treatment for 3 weeks) plants of P. odorifer to understand the role of ion distribution, ion transport, and related mechanisms under salt stress. Using a combination of ionomics and transcriptomics approaches, we identified the molecular mechanisms contributing to the high salinity stress in P. odorifer. Under NaCl stress, there was a significant increase in Na, Cl, and other ions in leaves, while the concentrations of Si, Fe, Ni, and Ti decreased. Similarly, in roots, the levels of Na, Mg, Cd, and Cr were significantly high, while the levels of other ions decreased. Most of the genes related to ion transport and homeostasis, such as NHX1, CLC-C, SOS1, HAK, and ABC transporters, were upregulated in 1 M NaCl stress conditions. This study revealed that vacuolar sequestration of Na+ and the distribution of ions in the roots and shoots play significant roles in the salt-stress tolerance mechanism of P. odorifer.
Keywords: Ion transport; Ionomics; Pandanus; Salinity tolerance; Transcriptomics; Vacuolar sequestration

Trehalose transporter-like gene diversity and dynamics enhances stress response and recovery in Helicoverpa armigera - Tellis, Meenakshi B.; Chaudhari, Bhagyashri Y.; Deshpande, Shweta V.; Nikam, Sanika V.; Barvkar, Vitthal T.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Gene, 2023)
Trehalose is a primary sugar and its distribution across the insect body, regulated by trehalose transporters (TRETs), is essential for sugar metabolism and energy homeostasis. The large diversity of Tret-like sugar trans-porters (ST), belonging to SLC2A transporter family, in polyphagous insects probably contributes to their extremely adaptive nature. We aim to study spatio-temporal expression dynamics and functional relevance of ST transcript variants in the lepidopteran model organism, Helicoverpa armigera. Identification of 69 putative Tret-like HaST transcript variants from databases and their digital gene expression analysis indicated tissue and development-specific expression patterns. Phylogenetic and sequence similarity network analysis of HaSTs signify evolutionary divergence, while motif and structure analysis depicted conserved signatures. In vitro gene expression validation for selected genes depicts that HaST09 and 69 are fat body and haemolymph-specific. While, HaST06, 30, 36 and 57 are developmental stage or sex-specific. HaST69 has high expression in the haemolymph of fifth instar larvae. In the presence of trehalose metabolism inhibitors and abiotic stress, HaSTs expression show dysregulation, indicating their possible association with trehalose metabolism and stress re-covery. In vivo gene silencing of HaST69 resulted in reduced trehalose accumulation in the insect body, sug-gesting its plausible role in sugar metabolism. The overall understanding of HaST diversity and expression dynamics highlights their putative roles in sugar transport during adaptation and stress recovery of insects.
Keywords: Gene expression; Helicoverpa armigera; Stress; Transporter-like; trehalose

Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Kallure, Gopal S.; Sahoo, Shubhranshu Shekhar; Kale, Rutuja S.; Barvkar, Vitthal T.; Kontham, Ravindar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2024)
One of the most prevalent bioactive molecules present in the oral secretion (OS) of lepidopteran insects is fatty acid amino acid conjugates (FACs). Insect dietary components have influence on the synthesis and retaining the pool of FACs in the OS. We noted differential and diet-specific accumulation of FACs in the OS of Helicoverpa armigera by using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Interestingly, we identified FACs hydrolyzing enzyme aminoacylase (HaACY) in the OS of H. armigera through proteomic analysis. Next, we have cloned, expressed, and purified active recombinant HaACY in the bacterial system. Recombinant HaACY hydrolyzes all the six identified FACs in the OS of H. armigera larvae fed on host and non-host plants and releases respective fatty acid and glutamine. In these six FACs, fatty acid moieties vary while amino acid glutamine was common. Glutamine obtained upon hydrolysis of FACs by HaACY might serve as an amino acid pool for insect growth and development. To understand the substrate choices of HaACY, we chemically synthesized, purified, and characterized all the six FACs. Interestingly, rHaACY also shows hydrolysis of synthetic FACs into respective fatty acid and glutamine. Our results underline the importance of diet on accumulation of FACs and role of aminoacylase(s) in regulating the level of FACs and glutamine.
Keywords: Aminoacylase; Fatty acid amino acid conjugates; Glutamine; Helicoverpa armigera; Oral secretion

Genome sequencing and protein modeling unraveled the 2AP biosynthesis in Bacillus cereus DB25 - Dhondge, Harshal V.; Barvkar, Vitthal T.; Dastager, Syed G.; Dharne, Mahesh S.; Rajput, Vinay; Pable, Anupama A.; Henry, Robert J.; Nadaf, Altafhusain B. (International Journal of Food Microbiology, 2024)
2-Acetyl-1-pyrroline (2AP) is an important and major flavor aroma compound responsible for the fragrance of basmati rice, cheese, wine, and several other food products. Biosynthesis of 2AP in aromatic rice and a few other plant species is associated with a recessive Betaine aldehyde dehydrogenase 2 (BADH2) gene. However, the literature is scant on the relationship between the functional BADH2 gene and 2AP biosynthesis in prokaryotic systems. Therefore, in the present study, we aimed to explore the functionality of the BADH2 gene for 2AP biosynthesis in 2AP synthesizing rice rhizobacterial isolate Bacillus cereus DB25 isolated from the rhizosphere of basmati rice (Oryza sativa L.). Full-length BcBADH2 sequence was obtained through whole genome sequencing (WGS) and further confirmed through traditional PCR and Sanger sequencing. Then the functionality of the BcBADH2 gene was evaluated in-silico through bioinformatics analysis and protein docking studies and further experimentally validated through enzyme assay. The sequencing and bioinformatics analysis results revealed a full-length 1485 bp BcBADH2 coding sequence without any deletion or premature stop codons. Full-length BcBADH2 was found to encode a fully functional protein of 54.08 kDa with pI of 5.22 and showed the presence of the conserved amino acids responsible for enzyme activity. The docking studies confirmed a good affinity between the protein and its substrate whereas the presence of BcBADH2 enzyme activity confirmed the functionality of BADH2 enzyme in B. cereus DB25. In conclusion, the findings of the present study suggest that B. cereus DB25 is able to synthesize 2AP despite a functional BADH2 gene and there may be a different molecular mechanism responsible for 2AP biosynthesis in bacterial systems, unlike that found in aromatic rice and other eukaryotic plant species.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice flavor; Betaine aldehyde dehydrogenase 2; Protein-ligand docking; Rhizobacteria; Whole-genome sequence

Ocimum kilimandscharicum 4CL11 negatively regulates adventitious root development via accumulation of flavonoid glycosides - Lavhale, Santosh G.; Kondhare, Kirtikumar R.; Sinthadurai, Veenothini S.; Barvkar, Vitthal T.; Kale, Rutuja S.; Joshi, Rakesh S.; Giri, Ashok P. (Plant Journal, 2024)
4-Coumarate-CoA Ligase (4CL) is an important enzyme in the phenylpropanoid biosynthesis pathway. Multiple 4CLs are identified in Ocimum species; however, their in planta functions remain enigmatic. In this study, we independently overexpressed three Ok4CL isoforms from Ocimum kilimandscharicum (Ok4CL7, -11, and -15) in Nicotiana benthamiana. Interestingly, Ok4CL11 overexpression (OE) caused a rootless or reduced root growth phenotype, whereas overexpression of Ok4CL15 produced normal adventitious root (AR) growth. Ok4CL11 overexpression in N. benthamiana resulted in upregulation of genes involved in flavonoid biosynthesis and associated glycosyltransferases accompanied by accumulation of specific flavonoid-glycosides (kaempferol-3-rhamnoside, kaempferol-3,7-O-bis-alpha-l-rhamnoside [K3,7R], and quercetin-3-O-rutinoside) that possibly reduced auxin levels in plants, and such effects were not seen for Ok4CL7 and -15. Docking analysis suggested that auxin transporters (PINs/LAXs) have higher binding affinity to these specific flavonoid-glycosides, and thus could disrupt auxin transport/signaling, which cumulatively resulted in a rootless phenotype. Reduced auxin levels, increased K3,7R in the middle and basal stem sections, and grafting experiments (intra and inter-species) indicated a disruption of auxin transport by K3,7R and its negative effect on AR development. Supplementation of flavonoids and the specific glycosides accumulated by Ok4CL11-OE to the wild-type N. benthamiana explants delayed the AR emergence and also inhibited AR growth. While overexpression of all three Ok4CLs increased lignin accumulation, flavonoids, and their specific glycosides were accumulated only in Ok4CL11-OE lines. In summary, our study reveals unique indirect function of Ok4CL11 to increase specific flavonoids and their glycosides, which are negative regulators of root growth, likely involved in inhibition of auxin transport and signaling.
Keywords: 4-Coumarate-CoA ligase; 7-O-bis-alpha-l-rhamnoside; adventitious root; auxin transport; Flavonoids; kaempferol-3; Ocimum kilimandscharicum; quercetin-3-O-rutinoside; rootless

Tyramine-mediated hyperactivity modulates the dietary habits in Helicoverpa armigera - Patil, Yogita P.; Gawari, Shyam K.; Barvkar, Vitthal T.; Joshi, Rakesh S. (JOURNAL OF CHEMICAL ECOLOGY, 2024)
Keywords: amines; Behavior; dopamine; octopamine; RECEPTOR; sensitivity; SULFAKININ

Altered Octopamine synthesis impairs tyrosine metabolism affecting Helicoverpa armigera vitality - Patil, Yogita P.; Wagh, Deepti S.; Barvkar, Vitthal T.; Gawari, Shyam K.; Pisalwar, Priyanka D.; Ahmed, Shadab; Joshi, Rakesh S. (Pesticide Biochemistry and Physiology, 2025)
Tyramine (1-hydroxylase (T(1H) is a key enzyme in the biosynthesis of octopamine (OA), a vital neurohormone in invertebrates. This study explores the expression patterns and functional role of Helicoverpa armigera T(1H (HaT(1H) across various tissues and developmental stages. HaT(1H expression was highest in the head and adult male stages, reflecting tissue-specific and developmental regulation. HaT(1H silencing significantly increased locomotion and decreased feeding behavior. OA supplementation in silenced insects or HaT(1H overexpression showed a contrary effect on locomotory and feeding behavior. In silico screening and inhibitory assays identified tomatidine, a tomato-derived metabolite, as a potent HaT beta H inhibitor with strong binding affinity. In vivo bioassays confirmed tomatidine's inhibitory effects, reducing feeding and increasing mortality in H. armigera. Modulation in HaT(1H expression or activity disturbs the tyrosine metabolic pathway, with altered levels of tyramine, octopamine, and dopamine. These results highlight HaT(1H as a key regulator of OA biosynthesis, influencing insect feeding, locomotion, and overall survival. The present study also introduces tomatidine as a potential candidate for insect control, given its ability to disrupt HaT beta H function. This work provides new insights into the physiological roles of HaT beta H and offers promising avenues for developing targeted pest management strategies.
Keywords: Helicoverpa armigera; Octopamine biosynthesis; Tomatidine; Tyramine (1-hydroxylase (HaT(1H); Tyrosine metabolic pathway

Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain B.; Kadoo, Narendra Y. (Journal of Plant Biochemistry and Biotechnology, 2025)
Salinity poses a formidable challenge to agriculture, detrimentally impacting plant growth and the yield of several crops globally. Pandanus odorifer (Forssk.) Kuntze is a highly salt-stress resilient plant that grows naturally along the coastal regions of Asia, Southeast Asia, and Polynesia. It is frequently found as a frontier species along the sandy shores receiving constant salt sprays. MicroRNAs (miRNAs) play essential regulatory roles in growth, development, and combating various biotic and abiotic stresses. Thus, characterizing miRNAs and their targets is critical to understanding their roles in salt stress tolerance. Through a rigorous analysis based on homology, secondary structure and signatures of other miRNA genes, we identified 52 conserved nonredundant miRNAs from the P. odorifer transcriptome data. These miRNAs were diverse and belonged to 23 miRNA phylogenetic families. Several miRNAs, including pod-MIR156a, pod-MIR164d, and pod-MIR535d, demonstrated distinct expression patterns in response to salt stress. Their target genes exhibited opposing expression trends, corroborating the intricate miRNA-target relationship. Delving deeper into their influence, we discovered that these miRNAs mainly targeted transcription factors that are known for their pivotal roles in stress responses. We also detected four miRNA-star (miRNA*) sequences (the complementary strands of functional mature miRNAs), which supports the authenticity of the identified miRNAs. This study unveils the intricate regulatory mechanism through which miRNAs may reinforce salt stress tolerance in P. odorifer, providing a promising avenue for enhancing crop resilience to various stresses through miRNA-based strategies.
Keywords: Abiotic stress; microRNA; miRNA targets; Salinity tolerance; salt stress; Transcription factors

High levels of sinigrin trigger synthesis of fatty acids in Plutella xylostella (L.) - Barve, Pranoti R.; Barvkar, Vitthal T.; Giri, Ashok P.; Kotkar, Hemlata M. (Comparative Biochemistry and Physiology D-Genomics & Proteomics, 2025)
Diamondback moth (Lepidoptera: Plutellidae; Plutella xylostella L.) is a specialist insect of the Brassicaceae family, damaging economically important crops, such as cabbage and cauliflower. Glucosinolates, also known as `mustard oil bombs' are present in all Brassicaceae members, of which sinigrin (allyl-glucosinolate or 2-propenylglucosinolate) is a major aliphatic compound. During herbivory, glucosinolates are converted to toxic isothiocyanates that deter insect pests. P. xylostella possesses glucosinolate sulfatases that desulfate them. Such a conversion renders them unfit for degradation to toxic products. Changes in the larval performance prompted us for RNA sequencing to understand probable adaptation mechanism under sinigrin stress. Differentially expressed genes were found to be related to larval cuticle proteins. Further, gene ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses depict genes belonging to the categories, integral component of membrane, cellular processes and those involved in biosynthesis of fatty acids. Upregulation of cuticular genes viz. larval cuticle protein-17 (LCP-17), cuticular protein-19 (2CP-19) and ATP binding cassette transporter C7 (ABCC7), ABCC16 was validated by qRT-PCR. Liquid chromatography quadrupole time of flight mass spectrometry analysis of whole larvae feeding on sinigrin and their separated cuticle, depicted abundance of fatty acids. Changes in the topography of the larval cuticle were evident by scanning electron microscopy. Expression of PxABCH1 was corroborated to its role in the transport of cuticular lipids. Notably, molecular docking of PxABCH1 with cuticular fatty acids showed favorable binding interactions. To summarize, integrated transcriptomic and metabolomic analyses suggest that in response to a diet containing a high dose of sinigrin, P. xylostella re-programs metabolic pathways related to fatty acid biosynthesis that directly influence insect development.
Keywords: ABC transporter; Cuticle; Host metabolite; Metabolome; Plutella xylostella; Sinigrin; Transcriptome

LDH-dsRNA nanocarrier-mediated spray-induced silencing of juvenile hormone degradation pathway genes for targeted control of Helicoverpa armigera - Joshi, Kaumudi S.; Barvkar, Vitthal T.; Hadapad, Ashok B.; Hire, Ramesh S.; Joshi, Rakesh S. (International Journal of Biological Macromolecules, 2025)
Helicoverpa armigera, a devastating agricultural pest, poses significant threats to global crop productivity. Targeting the Juvenile Hormone (JH) degradation pathway may offer a promising approach for pest management, given its pivotal role in insect development and reproduction. In this study, we developed a nanoclay-based formulation of double-stranded RNA (dsRNA) targeting three key JH degradation pathway genes: Juvenile Hormone Esterase (HaJHE), Juvenile Hormone Epoxy Hydrolase (HaJHEH), and Juvenile Hormone Diol Kinase (HaJHDK). Expression analysis revealed tissue and stage-specific patterns of these genes, with qRT-PCR confirming high expression levels of specific isoforms in key developmental transition: the pre-pupal stage. Treatment with bacterially expressed dsRNAs achieved >50 % silencing of target genes, resulting in delay in larval-to-pupal transitions. Bioassay demonstrated that treatment with LDH-based dsRNA nanocarrier resulted in downregulation of target genes, causing developmental delays, including prolonged larval and pupal stages. Metabolomic analysis further indicated reduced accumulation of JH degradation pathway metabolites, highlighting the pathway-specific action of dsRNAs. Furthermore, combinatorial application of dsRNAs resulted in higher mortalities compared to individual dsRNA application. These results suggest that the application of the LDH-based dsRNA nanocarrier formulation against H. armigera JH degradation pathway for spray-induced gene silencing could serve as a potential insect management strategy.
Keywords: Development; dsRNA; Helicoverpa armigera; Juvenile hormone; Layered double hydroxide; Nanocarrier

Mechanistic insights in the role of trehalose transporter in metabolic homeostasis in response to dietary trehalose - Chaudhari, Bhagyashri Y.; Nichit, Vikram J.; Barvkar, Vitthal T.; Joshi, Rakesh S. (G3-Genes Genomes Genetics, 2026)
Trehalose is the major sugar in insect hemolymph and plays a diverse role. Its level is regulated by the dynamics of biosynthesis and distribution by sugar transporters. The metabolic balance between trehalose synthesis and uptake remains poorly understood, despite its critical role in homeostasis. Here, we examined the role of the putative gut-specific sugar transporter, HaST46, in regulating trehalose levels in Helicoverpa armigera, a model Lepidopteran pest. Analysis of publicly available transcriptomics, proteomics data, and qRT-PCR study suggests that HaST46 showed localization in the posterior midgut and its expression alters in response to dietary contents. The liquid chromatography-mass spectrometry (LC-MS) analysis of HaST46 overexpressing Sf9 cells indicated that trehalose transport is preferred over glucose. HaST46 expression was found to be modulated tissue-specific manner in response to dietary trehalose availability. Furthermore, trehalose synthesis genes were found to be downregulated in the case of a 50 mM trehalose diet. This suggests that a potential increase in exogenous trehalose uptake may attenuate its endogenous synthesis. HaST46 overexpression and silencing lead to altered trehalose levels in the insect, while also having impact on trehalose metabolizing enzymes. Overall, our findings reveal the role of gut predominant sugar transporter, HaST46, in metabolic fine-tuning between exogenous trehalose uptake and endogenous synthesis.
Keywords: gut; Helicoverpa armigera; Metabolism; sugar uptake; transporters; trehalose